PROBLEMS OF EMPLOYMENT AND UNEMPLOYMENT ON THE GLOBAL PANDEMIC BACKGROUND IN GEORGIA (Globalization and Business, 2023)
In this article current negative processes, causes of deteriorating of employment and unemployment indications, the reasons of which take place in Economical and Social sphere due to outbreak of the novel Coronavirus, are briefly characterized. It was concluded that the country will not be insured from viral pandemics in the future, therefore, the state is obliged to do everything for cohabiting along with this or another virus. At the same time, it is necessary to ensure both -protection of public health, as well as the unhindered growth of the country's economy. We completely agree to the opinions of the Academician V. Papava, Expert I. Archvadze and others, that it is necessary to make more investments in the real sector of development of the country, especially in the agriculture, small and medium-sized businesses in general, which need to be developed more in the regions than in the capital. In addition to our opinion, along with the encouragement of exports, it is necessary to sharply reduce the volume of goods imported into the country, which will be possible through the development and implementation of production programs in our country (in Georgia). Effective regulation of employment and unemployment would not be impossible if such specific measures are not taken in this direction as: 1) Taking into consideration the consequences of the novel Coronavirus pandemic, it is necessary to specify the deadlines for the implementation of the “Georgian Labor and Employment Policy Strategy” within 2019-2023 (Resolution # 662, Annex 1) approved by the Government of Georgia on December 30, 2019; Due to the circumstances created in the country, the deadlines for the implementation of a lot of measures, set out in this Annex, should be extended. In addition, it is doubtfully to fully perform the functions established by the LEPL - Employment Agency in October 2019, envisaged by its statute for a variety of reasons (imposed complicated tasks, insufficient legal basis, weak supervision of the curatorial Ministry and etc.); 2) timely adoption of the Law "About Employment"; 3) It is necessary to specify the supervisor of labor, employment and unemployment issues in the country, the organizational structure and functions of the “Ministry of Refugees from the Occupied Territories, Labor, Health and Social Affairs” needs to be regulated; 4) In order to gradually implement the problems of unemployment, it is necessary to develop and implement employment programs on a regional scale. In this matter, the above-mentioned Ministry should perform not only a "Supporting", but an organizational role as well.